CC Chemokine Receptors in Lung Adenocarcinoma: The Inflammation-Related Prognostic Biomarkers and Immunotherapeutic Targets - Liu F (Dove Medical Press, 2021)
Fangteng Liu,1,2 Hengyu Wu1 1Department of Breast Surgery, The Third Hospital of Nanchang, Nanchang, Jiangxi, 330009, People’s Republic of China; 2Faculty of Medicine, University of Munich, Munich, 80336, GermanyCorrespondence: Hengyu Wu Tel +86-15270280590Email why_wuhengyu0590@163.comBackground: Lung adenocarcinoma (LUAD) is the most common type of lung cancer with a high incidence and increased mortality. CC chemokine receptors were participating in the modulation of the tumor microenvironment and involved in carcinogenesis and tumor development. However, the potential mechanistic values of CC chemokine receptors as clinical biomarkers and therapeutic targets in LUAD have not been fully clarified.Methodology: ONCOMINE, UALCAN, GEPIA, Kaplan–Meier Plotter, SurvExpress, MethSurv, SurvivalMeth, cBioPortal, String, GeneMANIA, DAVID, Metascape, TRRUST, LinkedOmics, and Timer were applied in this work.Results: The transcriptional levels of CCR1/10 in LUAD tissues were significantly reduced while the transcriptional levels of CCR3/6/7/8 were significantly elevated, and the expression of CCR1 was the highest in LUAD among these CC chemokine receptors. A significant correlation was found between the expression of CCR2/4/6/7 and the pathological stage of LUAD patients. There were significant associations between CCR2/3/4/5/6/10 expression levels and OS in LUAD, and LUAD patients with high transcriptional levels of CCR3/4 had inferior first-progression survival. In addition, the prognostic values of CC chemokine receptors signature in LUAD were explored in three independent cohorts, the high-risk group displayed unfavorable OS compared with the low-risk group, and the LUAD cases in the high-risk group also suffered inferior RFS than that in the low-risk group. And for the prognostic value of the DNA methylation of CC chemokine receptors, we found 1 CpG of CCR2, 2 CpGs of CCR3, 1 CpG of CCR4, 3 CpGs of CCR6, 3 CpGs of CCR7, 1 CpG of CCR8, and 3 CpGs of CCR9 were significantly associated with prognosis in LUAD patients. However, the DNA methylation signature analysis showed there was no statistically significant association between the high- and low-risk group. For potential mechanism, the neighbor gene networks, interaction analyses, functional enrichment analyses of CC chemokine receptors in LUAD were performed, the transcription factor targets, kinase targets, and miRNA targets of CC chemokine receptors were also identified in LUAD. We also found significant correlations among CC chemokine receptors expression and the infiltration of immune cells, the tumor infiltration levels among LUAD with different somatic copy number alterations of these chemokine receptors were also assessed. Moreover, the Cox proportional hazard model showed that CCR1/2/10, B_cell, CD4_Tcell were significantly related to the clinical outcome of LUAD patients.Conclusion: CC chemokine receptors might serve as immunotherapeutic targets and prognostic biomarkers in LUAD.Keywords: CC chemokine receptors, lung adenocarcinoma, prognostic biomarker, immunotherapeutic target, bioinformatics analysis